The Application Modular Floating Pontoon to Support Floods Disaster Evacuation System in Heavy Populated Residential Area - Ahmad Fauzan Zakki; Aulia Windyandari (Chemical Engineering Diponegoro University, 2014)
During floods disaster in the heavy populated residential area, the lack of existing life saving appliances system such as rubber boat and wooden boat were not able to evacuate the disaster victims spontaneously in mass. The condition might be explained since the rubber boat and wooden boat have limited occupant capacity. Based on the conditions, the main objectives of the research are focused on the evaluation of the application of modular floating pontoon as multipurpose floating equipment to support floods disaster evacuation process. The investigation of the modular floating pontoon performance such as hydrostatics characteristics, the equilibrium condition and the intact stability was studied using strip theory and Krylov’s method. Furthermore, the strength analysis of the modular floating pontoon structure was calculated using finite element method. The results show that the modular floating pontoon is reliable to support the evacuation process.